Pengaruh Kualitas Produk, Harga, Promosi, Desain Produk dan Citra Merek Smartphone Samsung Tipe A Terhadap Minat Beli Masyarakat Kota Padang - Putri, Radiyatul Nadiya; Jolianis, Jolianis; Ronald, Jimi (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2024)
This research aims to analyze (1) the effect of product quality on customer satisfaction, (2) the effect of service quality on customer satisfaction, (3) the effect of price on customer satisfaction, (4) the effect of promotion on customer satisfaction, (5) the effect of location on satisfaction customers, (6) the influence of product quality, service quality, price, promotion and location together on customer satisfaction for Sanjai Balado Ummi Aufa Hakim Chips, Padang City.This type of research is associative, the population in this research is customers who buy directly from the Ummi Aufa Hakim shop in Padang City, totaling 120 samples. Sampling used a purposive sampling technique, the instrument used for research was a closed questionnaire using the Multiple Linear Regression test and hypothesis testing using the t test and f test.